Development of Graphene/CdSe Quantum Dots‐Co Phthalocyanine Nanocomposite for Oxygen Reduction Reaction. Issue 10 (26th September 2014) - Nyoni, Stephen; Nyokong, Tebello
Abstract Nanocomposites containing CdSe quantum dots, tetra(4‐(4, 6‐diaminopyrimidin‐2‐ylthio) phthalocyaninatocobalt(II)) (CoPyPc) and reduced graphene nanosheets (rGNS) were devoloped and used for the modification of a glassy carbon electrode. Characterization of the nanocomposites was done by transmission electron microscopy (TEM) and X‐ray diffraction (XRD) analyses. Cyclic voltammetry (CV) was used for electrochemical characterization of the prepared nanocomposite for oxygen reduction reaction. The oxygen reduction activity for rGNS/CdSe‐CoPyPc nanocomposite was found to be superior over the individual nanomaterials in this study. The activity of the nanocomposite towards oxygen reduction was also tested for tolerance to methanol crossover effect using chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS) studies.